The Effect of Internal Audit Characteristics on the Budgeting Timeliness, Corruption, and Performance of Local Governments in Indonesia - Sutaryo, Sutaryo (Universiti Malaysia Sarawak, 2023)
The study aims to investigate the effect of local government internal auditor characteristics as represented by the capability, maturity, expertise, and size on local government accountability that consist of budgeting timeliness, corruption, and performance. The study uses secondary data from 514 local governments during 2010-2020 obtained from the publications and assessment results from the authorised government institutions. A total of 5,654 observations are analysed with panel data regression analysis. The results of this study suggest that internal auditor characteristics contributes to the local government accountability by having punctual budgeting timeliness, less corruption, and higher performance. Local government budgeting timeliness is supported by the internal auditor capability, maturity, and expertise, proven with positive effect. Local government internal auditor, through its capability, expertise, and size, also contributes to corruption eradication as the analysis demonstrates negative effect. Further, internal auditor capability, maturity, and expertise also positively affects performance. The study provides contribution to the literature by filling the limitation in prior studies as it presents comprehensive analysis that covers all Indonesian local governments with a long examination period. This study also brings implications to the local government to establish an internal audit function with capability, maturity, expertise, and adequate human resources in accordance with the workloads, complexity, and budget. Financial and Development Supervisory Agency should provide proper development programs for internal auditors and issue a regulation concerning internal auditor requirements and practice. Finally, the study provide recommendation for the Supreme Audit Board in regards with the external audit assignment by considering internal auditor characteristics in determining audit risk, samples and evidences.